PENGARUH MEDIA SOSIAL DALAM PENINGKATAN MAHARAH KALAM MAHASISWA SEMESTER 5 PENDIDIKAN BAHASA ARAB - Hidayah, Aidah Rahmah Hidayah; Muhamad Rizki Sahriya Ramadan; Shafa Salsabil Afifah; Wahyu Hidayat (Kampus Akademik Publiser, 2025)
This study aims to explore the effect of social media use on improving students' maharah kalam (speaking ability) in Arabic. The approach used is descriptive quantitative with data collection through surveys, questionnaires, semistructured interviews, and observations. The research subjects consisted of 5th semester students of the Arabic Language Study Program who actively use various social media platforms such as YouTube, Instagram, and WhatsApp to learn and practice Arabic. The results show that students who regularly interact with Arabic content on these platforms experience significant improvements in the aspects of pronunciation, vocabulary enrichment, and increased confidence in speaking. YouTube provides access to mimic correct pronunciation through learning videos, while Instagram and TikTok introduce vocabulary and expressions used in everyday social contexts. WhatsApp allows students to practice live conversations in Arabic, both through text and voice messages. The findings show that social media is not only a means of entertainment, but can also be an effective tool to improve Arabic speaking skills in a more natural, contextual and interactive way. This research provides insights into how social media platforms can be optimally utilized in language learning.